Photosynthetic responses of a golden tide alga (Sargassum horneri) to ultraviolet radiation - Xu, Zhiguang; Li, Lingxue; Jiang, Huichao; Yan, Fang; Liu, Lijuan; Zang, Shasha; Ma, Yuanqing; Wu, Hongyan (Frontiers in Marine Science, 2022)
In recent years, massive Sargassum drifting on the sea surface, known as “golden tides,” negatively impacted on the local marine ecology. However, the physiological mechanisms of its formation remain unclear. To investigate the photosynthetic responses of golden tide algae to UVR, one key factor for drifting Sargassum population, we cultivated thalli of S. horneri, a golden tide alga, under three light treatments: P (photosynthetically active radiation, PAR), PA (PAR+UVA) and PAB (PAR+UVA+UVB) for 120 mins, followed by low light recovery for 240 mins. The photosynthetic characteristics of alga were determined. The results showed that UVR exposure decreased photosynthetic activity, reflected by depressed maximum photochemical quantum yield (Fv/Fm) and contents of Chla and Chlc in the PA and PAB treatments. Higher content of malondialdehyde (MDA) was found in thalli exposed to UVR, which verified the damage of UVR. Electron transfer rate (ETR) was slowed down by UVR, accompanied by the increments of net closing rate of the reaction center and the energy absorbed and dissipated by unit reaction center in PSII. In these effects on photosynthesis of UVR, the PAB treatment expressed more significant inhibition, indicating a remarkable role of UVB. However, based on our results, S. horneri also took some strategies to protect itself from photodamage of UVR. UVR exposure enhanced the contents of UV-absorbing compounds (UVACs) and carotenoid, and simultaneously expedited heat consumption of excess light energy, indicated by the increased non-photochemical quenching coefficient (NPQ) in the PA and PAB treatments. Increased activities of superoxide dismutase (SOD) and peroxidase (POD), and higher content of PsbA (D1) protein were found in the treatments with UVR, which suggested that antioxidant system and the turnover of D1 protein played important roles in protection from UV-induced damages. Due to the above protection pathways, Fv/Fm and ETR gradually recovered when thalli were transferred to low light recovery. Therefore, we suggest that various protection and restoration pathways in S. horneri work together to effectively protect against UVR damage, which may be the reason why drifting populations can adapt to UVR on the seawater surface and form golden tide in case of suitable temperature and nutrients.